2019
DOI: 10.1186/s12888-019-2087-6
|View full text |Cite
|
Sign up to set email alerts
|

The cytokine profile of women with severe anxiety and depression during pregnancy

Abstract: Background Controversial findings regarding the association between pro-inflammatory cytokines and depression have been reported in pregnant subjects. Scarce data about anxiety and its relationships with cytokines are available in pregnant women. To understand the association between anxiety and cytokines during pregnancy, we conducted the present study in women with or without depression. Methods Women exhibiting severe depression (SD) and severe anxiety (SA) during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 50 publications
4
49
2
2
Order By: Relevance
“…In line with this, recent studies from our group showed that pregnant women exhibiting high levels of anxiety symptoms and severe depression in the third trimester of pregnancy displayed an increase of different subsets of Th1, Th2, Th17 and Treg-related immune biomarkers [72]. However, in the present study we showed that a similar related population displaying only severe anxiety, but not depression, showed a significant increase in CORT/DHEA-S index when compared to non-anxious pregnant women.…”
Section: Discussionsupporting
confidence: 79%
“…In line with this, recent studies from our group showed that pregnant women exhibiting high levels of anxiety symptoms and severe depression in the third trimester of pregnancy displayed an increase of different subsets of Th1, Th2, Th17 and Treg-related immune biomarkers [72]. However, in the present study we showed that a similar related population displaying only severe anxiety, but not depression, showed a significant increase in CORT/DHEA-S index when compared to non-anxious pregnant women.…”
Section: Discussionsupporting
confidence: 79%
“…Mental health during pregnancy (e.g., stress, anxiety, pregnancy-related anxiety, and depression) can influence birth outcomes [ 1 ] including preterm birth [ 2 , 3 ] and low birth weight [ 3 ]. Limited studies examining the role of comorbid anxiety and depression in this literature indicate comorbid anxiety and depression may further increase the risk of preterm birth or low birth weight [ 4 , 5 ]. Studies examining immune system pathways to preterm birth demonstrate the plausibility, as a correlation exists between cytokines such as interleukin-6 and interluken-12 and depression, anxiety and perceived stress measured in the second [ 6 ] or third [ 4 ] trimester.…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies examining the role of comorbid anxiety and depression in this literature indicate comorbid anxiety and depression may further increase the risk of preterm birth or low birth weight [ 4 , 5 ]. Studies examining immune system pathways to preterm birth demonstrate the plausibility, as a correlation exists between cytokines such as interleukin-6 and interluken-12 and depression, anxiety and perceived stress measured in the second [ 6 ] or third [ 4 ] trimester. Furthermore, cytokine levels were higher in women with comorbid anxiety and depression when compared to women with anxiety only [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations